BS ISO 17208-1 AMD 1. Underwater acoustics. Quantities and procedures for description and measurement of underwater sound from ships. Part 1. Requirements for precision measurements in deep water used for comparison purposes (28th February 2023) - British Standards Institution,
No abstract available